Papain Affects the Percentage and Morphology of Microglia in Hippocampal Neuron–Glial Cultures - Ivan A. Tumozov; Valentina N. Mal’tseva; Sergei A. Maiorov; Artem M. Kosenkov; Sergei G. Gaidin (Brain Sciences)
Background. Microglia, accounting for 5–15% of total brain cells, represent an essential population of glial cells in the cultures used for modeling neuroinflammation in vitro. However, microglia proliferation is poor in neuron–glial cultures. Here, we studied the population composition of rat hippocampal neuron–glial cell cultures prepared utilizing papain (PAP cultures) and trypsin (TRY cultures) as proteolytic enzymes for cell isolation. Methods. To evaluate the percentage and morphology of microglia in TRY and PAP cultures and cultures incubated in the presence of TGFβ+MCSF+cholesterol, which should enhance microglia proliferation, we used an immunostaining and calcium imaging approach in combination with staining using the recently developed vital microglia fluorescent probe CDr20. Results. We have shown that the microglia percentage in PAP cultures was higher than in TRY cultures. Microglia in PAP cultures are predominantly polarized, while bushy morphology was more characteristic of TRY cultures. We have also demonstrated that the TGFβ+MCSF+cholesterol combination increases the microglia number both in PAP and TRY cultures (up to 25–30%) and promotes the appearance of ameboid microglia characterized by high mobility. However, the significant appearance of ameboid microglia was observed already at the early stages of cultivation (2 DIV) in TRY cultures, while in PAP cultures, the described transformation was observed at 7 DIV. Based on the absence of the ATP-induced Ca2+ response, round shape, significant proliferation, and high mobility, we have suggested that ameboid microglia are reactive. Conclusions. Thus, our results demonstrate that papain is a more suitable proteolytic enzyme for preparing mixed hippocampal neuron–glial cultures with a higher percentage of heterogeneous microglia and functional neurons and astrocytes (tricultures).